Relevance of small GTPase Rac1 pathway in drug and radio-resistance mechanisms: Opportunities in cancer therapeutics - Cardama, Georgina Alexandra (2018)
Rac1 GTPase signaling pathway has a critical role in the regulation of a plethora of cellular functions governing cancer cell behavior. Recently, it has been shown a critical role of Rac1 in the emergence of resistance mechanisms to cancer therapy. This review describes the current knowledge regarding Rac1 pathway deregulation and its association with chemoresistance, radioresistance, resistance to targeted therapies and immune evasion. This supports the idea that interfering Rac1 signaling pathway could be an interesting approach to tackle cancer resistance.